Prescribing Antibiotics for Children with Acute Conditions in Public Primary Care Clinics in Singapore: A Retrospective Cohort Database Study - Vivien Min Er Lee; Si Hui Low; Sky Wei Chee Koh; Anna Szuecs; Victor Weng Keong Loh; Meena Sundram; José M. Valderas; Li Yang Hsu (MDPI AG, 2024)
Data on primary care antibiotic prescription practices for children in Singapore, which are essential for health care policy, are lacking. We aimed to address this gap and to benchmark prescription practices against international standards. A retrospective cohort database study on antibiotic prescriptions for children (aged < 18 years) who visited six public primary care clinics in Singapore between 2018 and 2021 was conducted. Data were categorised according to the World Health Organization's Access, Watch, Reserve (WHO AWaRe) classification. Quality indicators from the European Surveillance of Antimicrobial Consumption Network (ESAC-Net) and the National Institute for Health and Care Excellence (NICE) guidelines were used as a measure of appropriateness of antibiotic prescribing at the individual and overall patient level. In 831,669 polyclinic visits by children between 2018 and 2021, there was a significant reduction in mean antibiotics prescribed per month during pandemic years (2020-2021) compared to pre-pandemic (2018-2019) (MD 458.3, 95% CI 365.9-550.7). Most prescriptions (95.8%) for acute conditions fell within the WHO AWaRe "Access" group. Antibiotic prescription significantly exceeded (55.2%) the relevant quality indicator for otitis media (0-20%). The proportion of children receiving appropriate antibiotics for acute respiratory infections (n = 4506, 51.3%) and otitis media (n = 174, 49.4%) was low compared to the quality indicator (80-100%). There is a need to develop local evidence-based primary care antibiotic guidelines, as well as to support the development of stewardship programmes.